Diseño de pozo direccional esg-4 y selección del taladro de perforación - Velez Vera, Jimmy Daniel (2009)
This paper presents the design of a directional well, from a cellar chosen in surface to subsurface primary target and from this design the proper selection of drill drilling, compliance with technical security, minimal costs, utilities and environmental security. For this, was gathering information from wells correlation previously drilled at the location; useful information, such as surveys, drilling bits used in these, casings designs, depths of tops of each one of the formations crossed, rheological and hydraulic properties, bottom hole assemblies and directional profiles of these wells; to have at the end a summary of all the problems that caused a delay or financial loss in the drilling, this way, as a basis to make the directional wells design, being this compilation, a guide or a prevention for future errors. Finally, be designed and be selected, the directional profile, the casings, the hydraulics, bottom hole assemblies, volumes of cement, the application for funds to drill the well and a brief estimate of costs and operation time, in order to perform a technical analysis of the available drill drilling, and if this meets the needs of the well, otherwise, recommend the drilling equipment according to the required design.